Power and imbalances in the global monetary system : a comparative capitalism perspective - Vermeiren, Mattias; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The author examines the indirect macroeconomic roots of the global financial crisis and Eurozone debt crisis: the escalation of global trade imbalances between the US and China and regional trade imbalances in the Eurozone. He provides new insights into the sources and dynamics of power and instability in the contemporary global monetary system.
Keywords: Science